Creatine and other supplements - Lattavo, A.; Kopperud, A.; Rogers, P. D. (Pediatric Clinics of North America, 2007)
Ergogenic dietary supplement use is highly prevalent among adolescent and collegiate athletes, and use is increasing. To make appropriate recommendations for or against use by individual athletes, physicians who work with adolescent athletes should be knowledgeable about the most commonly used supplements and be able to access high-quality information about others. This article first discusses the legal and regulatory environment of dietary supplements. Several of the most commonly used supplements are then discussed in detail, including creatine, beta-hydroxy-beta-methylbutyrate, protein, amino acids, stimulants, alkalotic agents, glycerol, vitamins, and minerals. Finally, the "Gateway Theory" as it may relate to adolescent supplement and other drug use is discussed.